Halal Value Chain in the Holding Business: The Experience of Islamic-based School (Pesantren) in Indonesia - Kholilah Kholilah; Kurniawati Meylianingrum; Tiara Juliana Jaya; Ahmed Tahiri Jouti (Shirkah: Journal of Economics and Business, 2022)
This study constitutes a novel concept that provides a complete analysis of the holding business at an Islamic-based school (Pesantren) and the halal value chain. The halal value chain provides a standard for sharia-compliant production, distribution, or consumption activities. This case study was based in Pesantren Al-Rifa’ie, addressed in Malang East Java Indonesia. This study collected data through interviews, contract data, SOP, financial statements, BMT reports, and observation. The data were analyzed using the heuristic case study. The results showed that the holding business at Pesantren Al-Rifa'ie was in the form of a cooperative since it combines business units. The cooperative has funding, financing, and BMT activities. BMT is profit-oriented through establishing business units. Business units supporting the halal value chain were husbandry, bus rentals, and One Pesantren One Product (OPOP) starting from the input, process, and output. This research strengthens the New Institutional Theory and provides insight into the need for technical requirements to establish the company holding in Pesantren.